Resensitization of cisplatin resistance ovarian cancer cells to cisplatin through pretreatment with low‐dose fraction radiation. (2nd April 2019) - Zhao, Lili; Liu, Shihai; Liang, Donghai; Jiang, Tao; Yan, Xiaoyan; Zhao, Shengnan; Liu, Yuanwei; Zhao, Wei; Yu, Hongsheng
Abstract: Objective: Cisplatin is the first‐line chemotherapy for ovarian cancer. However, cisplatin resistance is severely affecting the treatment efficacy. FOXO3a has been reported to be involved in reversing chemotherapy resistance. However, whether low‐dose fraction radiation therapy (LDFRT) can reverse cisplatin resistance remains unclear. This study aimed to explore the effect of LDFRT on cisplatin resistance and its relation with FOXO3a expression in vitro. Methods: The toxicity of cisplatin on SKOV3/DDP cells was evaluated by CCK8 assay and cell apoptosis was measured by Annexin V‐FITC staining as well as Hoechst33342 staining. The expression of FOXO3a and other relative proteins was measured by western blot. Results: Our study found that LDFRT enhanced cisplatin‐induced apoptosis of SKOV3/DDP cells and promoted the expression of FOXO3a and pro‐apoptotic protein PUMA. In addition, overexpression of FOXO3a promoted PUMA activity and toxicity of cisplatin on SKOV3/DDP cells. Conclusion: LDFRT reverses cisplatin resistance of SKOV3/DDP cells possibly by upregulating the expression of FOXO3a and its downstream target PUMA, suggesting that LDFRT might be a potent chemosensitizer for the treatment of ovarian cancer. Abstract : LDFRT reverses cisplatin resistance of SKOV3/DDP cells possibly by upregulating the expressions of FOXO3a and its downstream target PUMA, suggesting that LDFRT might be a potent chemosensitizer for the treatment of ovarian cancer.